Memprediksi Tingkat Kelangsungan Usaha PT KAI Melalui Pendekatan Altman Z-Score - Haris, Haris author; Olfebri, Olfebri; Lestari, Riza (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
PT. Kereta Api Indonesia (PT. KAI) a State Owned Enterprises which currently is one of the major players in the ground transportation services industry has long been actively involved in the business of land transportation services. This study is limited in the scope of the analysis of the ratio-financial analysis, and then formulated using Alman z-score method. Ratio analysis is done based on financial data obtained from PT. Kereta Api Indonesia Indonesia ranging from 2012 to 2013. Then the figures obtained will be correlated with theories relevant financial, in order to obtain valid results that can be scientifically defensible. Furthermore, a comparison test as a reference in determining the potential failure of the items in the financial statements, and determine which of the posts have a strong and significant correlation. Media that can be used to examine the health condition of the company was a financial report consists of the Balance Sheet or Statement of Profit / loss, or results of operations, Cash Flow Statement, Statement of Changes in Financial Position. The financial reports produced by the management of a company is the end result of the process of business activities undertaken by the existing components in the company. The financial statements are made to account for the activities of the company to the owner and provide information about the financial position of the company has been achieved against the parties concerned. Keywords : Financial Performance and business sustainability